GLOBECOM 2017 - 2017 IEEE Global Communications Conference 2017
DOI: 10.1109/glocom.2017.8254173
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Number of Transmit Antennas for Secrecy Enhancement in Massive MIMOME Channels

Abstract: This paper studies the impact of transmit antenna selection on the secrecy performance of massive MIMO wiretap channels. We consider a scenario in which a multi-antenna transmitter selects a subset of transmit antennas with the strongest channel gains. Confidential messages are then transmitted to a multi-antenna legitimate receiver while the channel is being overheard by a multi-antenna eavesdropper. For this setup, we approximate the distribution of the instantaneous secrecy rate in the large-system limit. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 19 publications
1
11
0
Order By: Relevance
“…In [12] and [13], it was demonstrated that in several MIMO settings, energy efficiency is not an increasing function of the number of transmit antennas, and thus, it can be improved by switching off some of them. The authors in [14], moreover, showed that in MIMO wiretap settings, the secrecy performance, when no precoding is utilized at the Base Station (BS), is optimized when only a few transmit antennas are set active. The security benefits of optimal single antenna selection was further discussed in [15].…”
Section: Introductionmentioning
confidence: 99%
“…In [12] and [13], it was demonstrated that in several MIMO settings, energy efficiency is not an increasing function of the number of transmit antennas, and thus, it can be improved by switching off some of them. The authors in [14], moreover, showed that in MIMO wiretap settings, the secrecy performance, when no precoding is utilized at the Base Station (BS), is optimized when only a few transmit antennas are set active. The security benefits of optimal single antenna selection was further discussed in [15].…”
Section: Introductionmentioning
confidence: 99%
“…(10) and Equ. (13),C m,n+1 ≤C m,n holds, which indicates thatC m,n is monotonically decreasing with the increase of the number of the selected antennas. As Z n is the maximal value in each level, they are constants once the search tree is fixed.…”
Section: A Ncsiementioning
confidence: 96%
“…with a ǫ := −3q 0 ψ/ √ 2, the outage secrecy rate is a decreasing function of L, and therefore, L ⋆ = 1. Nevertheless, when (38) does not hold, the optimal number of active transmit antennas antennas is given by 1…”
Section: B Scenario Bmentioning
confidence: 99%
“…This work has been presented in part at GLOBECOM 2017 [1]. Saba Asaad and Amir Masoud Rabiei are with the School of Electrical and Computer Engineering (ECE), University of Tehran (UT), Tehran, Iran (e-mail: saba_asaad@ut.ac.ir).…”
Section: Introductionmentioning
confidence: 99%